FAMILY EDUCATIONAL INVOLVEMENT AND CHILD ACHIEVEMENT IN EARLY ELEMENTARY SCHOOL FOR AMERICAN‐BORN AND IMMIGRANT FAMILIES. Issue 8 (10th July 2014) - Sibley, Erin; Dearing, Eric
<x xml:space="preserve">Abstract</x> As the foreign‐born population in the United States grows, the achievement of immigrant children is a pressing concern. We examined family educational involvement in early elementary school as a potential source of support for the academic success of children in immigrant families. Using a nationally representative sample, we examined rates of educational involvement at first and third grade, as well as associations between involvement and math and reading achievement at these times. With regard to rates, the domain of greatest difference between U.S.‐born White parents and both U.S.‐born and immigrant parents of color (Asian, Black, and Latino) was for school‐based involvement. In addition, several variations in the associations between involvement and child achievement were evident across immigrant and race/ethnicity groups, with children in U.S.‐born White, Black, and Asian families as well as children in Latino immigrant families most consistently demonstrating positive associations between family educational involvement and achievement.